2019
DOI: 10.1090/bproc/40
|View full text |Cite
|
Sign up to set email alerts
|

The Erdős conjecture for primitive sets

Abstract: A subset of the integers larger than 1 is primitive if no member divides another. Erdős proved in 1935 that the sum of 1/(a log a) for a running over a primitive set A is universally bounded over all choices for A. In 1988 he asked if this universal bound is attained for the set of prime numbers. In this paper we make some progress on several fronts and show a connection to certain prime number "races" such as the race between π(x) and li(x).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Moreover, we prove similar results-comparing the logarithmic density of a set of real numbers to the relative logarithmic density of the primes lying in that set-for a number of other prime races, some of which have not been considered before (see Theorems 4.1 and 5.6). These results resolve some problems from [12] and so make progress on the Erdős conjecture on primitive sets (see Section 4).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Moreover, we prove similar results-comparing the logarithmic density of a set of real numbers to the relative logarithmic density of the primes lying in that set-for a number of other prime races, some of which have not been considered before (see Theorems 4.1 and 5.6). These results resolve some problems from [12] and so make progress on the Erdős conjecture on primitive sets (see Section 4).…”
Section: Introductionsupporting
confidence: 58%
“…In [12] it was conjectured that all primes are Erdős-strong. Since 2 is not a Mertens prime, it would be great progress just to be able to prove that 2 is Erdős-strong.…”
Section: The Mertens Racementioning
confidence: 99%
“…Zhang [13] proved that f (N 1 ) > f (N k ) for each k ≥ 2. Lichtman and Pomerance [7] proved that f (N k ) ≫ 1. Bayless, Kinlaw, and Klyve [2] recently showed that f (N 2 ) > f (N 3 ), providing bounds on f (N k ), f (N * k ) for small k. Here N * k is the set of squarefree k-almost primes.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], Erdős and Zhang showed that for any primitive sequence , and in [5], Clark improved this result (where γ is the Euler constant) in the special case when A is a primitive set of composite numbers. Several years later in [6],…”
Section: Introductionmentioning
confidence: 99%